The Relationships between Leader Creativity Expectations, Intrinsic Motivation, and Creative Performance - Muhammad Shahnawaz Adil; Kamal Bin Ab Hamid (SEISENSE Journal of Management, 2019)
Objective: The objectives of this conceptual paper are two folds: to propose and argue a) the direct relationship between leader creativity expectations and creative performance; and b) the mediating role of intrinsic motivation between leader creativity expectations and creative performance. Design: Drawing upon Pygmalion effect, Herzberg’s two-factor theory of motivation, and componential theory of creativity, two propositions are suggested. Findings: It is proposed that there will be a positive relationship between leader creativity expectations and creative performance. In addition, the authors also make the case that intrinsic motivation will mediate the relationship between leader creativity expectations and creative performance. Originality: The significant original contribution of this article is that it suggests a theoretical relationship of Pygmalion effect with Herzberg’s two-factor theory of motivation and componential theory of creativity to propose a new conceptual framework. In addition, this paper extends our knowledge regarding the pertinent role of leader creativity expectations in stimulating the divergent thinking process of people in the workplace. Policy Implications: This article attempts to provide a clear guideline to both practitioners and academicians to better explore the relationship between expectations and employee creativity. The proposed framework may be applied in various social contexts such as healthcare, education, creative advertising, research and development, hospitality and new business incubation.